Protection of the rights of children and minors in their transactions in the information society - Omelchuk, Oleksandr; Cherniak, Olena; Tyshcuk, Nataliia (Universidad Hemisferios, 2020)
The article is devoted to the analysis of features that arise when committing transactions by children and minors in the development of information society, identifying problems that arise when committing such transactions out of their legal capacity, as well as to the issue of the protection of violated rights and legitimate interests of children and minors due to the pandemic. The dialectical method of cognition, the method of system-structural analysis, he formal-logical method, the comparative-legal method, the method of logical analysis and dogmatic interpretation of legal norms were used preparing the article. The structure of the body of the text is comprised of such sections as introduction, methodology, analysis of recent research, results and discussion, conclusions. The main conclusion of the study is the establishing the need to clarify the amount of legal capacity of children and minors in different age groups. It is proposed to consolidate the division of minors into the following groups: from birth to 6 years; from 6 to 10 years; and from 10 to 14 years.